Penilaian Hasil Belajar Pendidikan Agama Islam: Kajian Konseptual Terhadap Implementasi Asesmen Kurikulum Merdeka - Mira Yulianti; Nurfarida Deliani; Juliana Batubara (Alpatih Harapan Semesta, 2026)
This research examines the assessment of learning outcomes in the Merdeka Curriculum as a systematic process to evaluate the cognitive, affective, and psychomotor achievements of students. Assessment not only determines graduation but also provides feedback for teachers and students to improve learning. The research uses a literature study method with a descriptive qualitative approach. Data were obtained from books, SINTA-accredited scientific journals from 2020–2026, and policy documents, specifically Permendikbudristek Number 21 of 2022. Data analysis used content analysis through data reduction, systematic data presentation, and conclusion drawing. The study results indicate that quality assessment must be valid, objective, fair, integrated, comprehensive, and accountable, and include diagnostic, formative, and summative assessments. Further research is recommended to examine the implementation of the Merdeka Curriculum assessment in various schools at the primary and secondary education levels, involving a variety of subjects, school contexts, and teacher readiness.